E-COMMERCE RUMAH KOMERSIL GREEN CENTER PARK BERBASIS ANDROID - Cezi Intan Sari; Faradillah Faradillah; Dhamayanti Dhamayanti (E-Link: Jurnal Teknik Elektro dan Informatika, 2024)
PT. Bangun Cipta Anugrah Abadi is a company that operates in the real estate sector and focuses on revenue and sales. PT. Bangun Cipta Anugrah Abadi is located in Ruko Perumnas Tl. Kelapa, Alang-Alang Lebar District, Palembang City. PT. Bangun Cipta Anugrah Abadi offers several housing products, including Green Center Park Housing located on Jalan Boulevard Citra Grand City No. 88, Alang-Alang Lebar Palembang. Currently, there is no system that helps customers easily place orders with booking agents without having to travel to the location. For this reason, an information system will be built for Android e-commerce of Commercial Homes based in Green Center Park using the Android Studio application, as a container for creating web services and facilities. MySQL database to create the database. Testing takes place using the black box method, including testing the admin system, users and the report printing process. From the test result, the feature menu in the green center park e-commerce application runs well and satisfies users in accordance with user expectations.